2013
DOI: 10.3324/haematol.2013.084533
|View full text |Cite
|
Sign up to set email alerts
|

Thalassemic erythrocytes release microparticles loaded with hemichromes by redox activation of p72Syk kinase

Abstract: © F e r r a t a S t o r t i F o u n d a t i o ndifferent genetic and clinical status provided new insights into the pathogenic role of circulating MP and possible interventions to control their amount in thalassemia. MethodsUnless otherwise stated, all materials were obtained from Sigma-Aldrich, St. Louis, MO, USA. Additional information about the methods are provided in the Online Supplementary Data. Treatment of red blood cellsVenous blood was drawn from 12 healthy individuals, eight non-splenectomized TI pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
81
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(96 citation statements)
references
References 47 publications
9
81
0
6
Order By: Relevance
“…We observed that antioxidant proteins, chaperone proteins, proteins involving in iron metabolism, hemoglobin subunit d, cathepsin S (an inflammatory marker), and erythroid proteins were consistently increased in quantity in HbE/ b-thalassemic patients across all 3 pooled samples (Table 2), and this was also observed in 6 individual samples (Table 4). Taken together, the observed alterations in protein content in the thalassemic EVs are consistent with the known increase in oxidative burden due to peripheral hemolysis reported in previous studies, 13,22,24 and this study has substantially extended the number of known proteins with an altered concentration in HbE/ b-thalassemic patients' EVs.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We observed that antioxidant proteins, chaperone proteins, proteins involving in iron metabolism, hemoglobin subunit d, cathepsin S (an inflammatory marker), and erythroid proteins were consistently increased in quantity in HbE/ b-thalassemic patients across all 3 pooled samples (Table 2), and this was also observed in 6 individual samples (Table 4). Taken together, the observed alterations in protein content in the thalassemic EVs are consistent with the known increase in oxidative burden due to peripheral hemolysis reported in previous studies, 13,22,24 and this study has substantially extended the number of known proteins with an altered concentration in HbE/ b-thalassemic patients' EVs.…”
Section: Discussionsupporting
confidence: 74%
“…13 In our study, we detected these proteins in at least twofold greater abundance in thalassemic EVs when compared with EVs from control individuals. The presence of these antioxidant proteins likely reflects the stressresponse mechanism in thalassemic erythrocytes, and we propose this could be a result of either EVs shedding from the viable erythrocytes or being generated from red cell lysis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…1. Вид эритроцитарных микровезикул из плазмы крови пациента с бета-талассемией при наблюдении в световой микроскоп (воспроизведе-но из [8]): а -флуоресцентная конфокальная микроскопия, б -классическая световая микроскопия. Шкала масштаба -1 µм Fig.…”
Section: O N C O H E M a T O L O G Y 1 ' 2017 V O L 1unclassified
“…1. Erythrocyte microvesicles from plasma of a patient with beta-talassemia as seen in an optical microscope (reproduced from [8]): a -fluorescence confocal microscopy, б -traditional light microscopy. Scale -µm…”
Section: O N C O H E M a T O L O G Y 1 ' 2017 V O L 1mentioning
confidence: 99%